Determination of soybean seed respiration rate by the titulation method - Crispim, Jack Eliseu; Martins, José Celso; Pires, José Carlos; Rosolem, Ciro Antônio; Cavariani, Claudio (Pesquisa Agropecuaria Brasileira, 1994)
This trial was carried out under laboratory conditions, with three lots of Iguaçu soybean seeds, to determine the respiration rate by the titulation method. A randomized complete block design was used, with four repetitions, each one of them with 50 seeds and a control without seeds for each lot. The seeds were placed in gerbox with 40 ml of KOH 0.1N, on distilled water wet blotting paper for fixing the CO2 produced by seeds respiration. The material was placed in germinator at constant 25°C for 16, 24 and 48 hours. After these periods, the titulation of the fixative solution was performed with HCl 0.1N to check the respiration rate. The most deteriorated seeds were those that presented the highest respiration rates, which were measured in mg of CO2/g of dry matter, when compared with the most vigorous lots. The titulation method was suitable for the evaluation of soybean seed respiration rate because the final results separated the lots in three different quality levels that were compatible with the results obtained from the accelerated aging and emergence.
Keywords: seed quality; CO2 fixing; germination; germinator; vigor